Война за океан: [роман] / Николай Задорнов - Задорнов Николай Павлович (Сибириада, 2016)
Экземпляры: 10 (20170817) / Инвентарный номер: 61851 / Цена: 209.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: З-15 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44